PENGEMBANGAN MOBILE APLIKASI OBAT ORAL ANTI KANKER DALAM PENERAPAN PATIENT CENTER CARE: A LITERATUR REVIEW - Lasiyani, Ni Luh; Rahman, La Ode Abdul (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p09, 2023)
Anti-cancer drugs have been developed in oral form. It is reported that the types of oral anti-cancer drug that are often used for the most cancer cases in the world such as hormonal groups, genetic mutation targets, and cytotoxic types. There are many benefits of this oral anti-cancer drug for patients, health workers, and drug providers. However, there are still challenges and obstacles such as the lack of patient understanding about drugs, low patient adherence to oral cancer therapy, and the limited number of health workers compared to the speed of increasing cancer cases. The purpose of this study was to determine the development of an Oral Agent for Cancer (OAC) mobile application for patient-centred care. This study uses a literature review method. The four databases used are ClinicalKey Nursing, ScienceDirect, EBSCOhost, and Scopus, using the keywords Cellular Application, Oral Agent for Cancer, Patient Centre Care and Technology. Literature review result shows that the use of mobile OAC applications increases patient motivation, actively participates in therapy, cost efficiency, time effectiveness, patient independence in managing side effects. From the nurse's point of view, although the number of personnel is limited, it’s show optimal quality of nursing care. The use of the OAC mobile application is effective in patient-centred care.